Energy Optimal Intelligent Switching Mechanism for Induction Motors with Time Varying Load. Issue 1 (August 2020) - Raja Singh, R.; Thanga Raj, C.; Palka, Ryszard; Indragandhi, V.; Wardach, Marcin; Paplicki, Piotr
Abstract: In medium and small process industries Induction Motor (IMs) enabled star-delta energy conservation scheme is a common practice. In such industrial applications, the Power Quality Disturbances (PQD) must be considered for hassle free operation. This paper is an attempt in the above direction on star-delta energy conservation applied to IMS (2.2 kW and 37.5 kW) operated with time varying loads. In apart to machine's performance evaluation, variation of switchover point for uninterrupted operation and optimized energy savings under various electrical perturbations is realized. Moreover, safe restarting feature is equipped in controller for resuming the machine during unplanned shutdown or any interruption.